Youth and adult literacy politics: MOBRAL instance at Riachuelo-RN county (Research, Society and Development, 2018)
This is an article about the MOBRAL program – Movimento Brasileiro de Alfabetização – at Riachuelo-RN municipality. The main aim is to understand this youth and adult literacy program operation in the municipality, analyzing its operation, teacher training, teaching methodology, classes constitution, identifying its pragmatic model inserted in the historical context.  The research methodology is mostly oral history based on oral and written interviews, narratives and testimonies from the main involved agents of MOBRAL. There were used other documents, such as photography and archives from the City Hall of Riachuelo-RN that allowed the dialogue with the oral sources, the framing and analysis of this program. Through this circumstances we acquired a local outlook at the operation of this public education policy from the military government at Riachuelo-RN, identifying its guidance and local attendance.